Three-dimensional mesoscale modelling of multi-span masonry arch bridges subjected to scour. (15th June 2018) - Tubaldi, Enrico; Macorini, Lorenzo; Izzuddin, Bassam A.
Highlights: Novel strategy for 3D analysis of masonry arch bridges under pier scour. Accurate and efficient description of the bridge components interaction. Evaluation of bridge response and cracking for increasing scour levels. Minor scour levels may affect more the stiffness than the capacity of the bridge. Abstract: Many masonry arch bridges cross waterways and are built on shallow foundations which are often submerged and exposed to the scouring action of the stream. The limited resistance of masonry arch bridges to foundation settlements makes them very vulnerable to scour and calls for the development of advanced tools for evaluating and improving the capacity against this flood-induced effect. This paper describes a novel three-dimensional modelling strategy for describing the behaviour of multi-span masonry arch bridges subjected to scour at the base of the pier shallow foundations. A mesoscale description is employed for representing the heterogeneous behaviour of masonry units, mortar joints and brick-mortar interfaces, whereas a domain partitioning approach allowing for parallel computation is used to achieve computational efficiency. The scouring process is described via a time-history analysis in which the elements representing the soil are progressively removed from the model according to a specific scour evolution. The proposed modelling approach is first employed to simulate available experimental tests on a dry masonry wall subjected to the settlement of the bearing system and on a reduced scale brick-masonry bridge specimen subjected to scour-induced pier settlements. Subsequently, a numerical example consisting of a multi-span arch bridge subjected to the scouring action is presented to illustrate the potential of the proposed modelling approach and its capabilities for evaluating the vulnerability and risk of masonry arch bridges under flood scenarios.